Optical and surface energy probe of Hamaker constant in copper oxide thin films for NEMS and MEMS stiction control applications - Abraham Ogwu (Nature Portfolio, 2021)
Abstract Copper oxide films hold substantial promise as anti-stiction coatings in micro-electromechanical (MEMS) devices and with shrinking dimensions on the nanometre scale on nano electromechanical (NEMS) devices. The Hamaker constant will play a very significant role in understanding stiction and tribology in these devices. We used an approximate but sufficiently accurate form of the Lifshitz theory using the multiple oscillator model to calculate the Hamakers constant of symmetric copper oxide thin films based on experimentally obtained dielectric data in the wavelength range 190-850 nm using spectroscopic ellipsometry. We also used the Tabor–Winterton approximation (TWA) and Surface energy measurements to determine the Hamaker constant. There was better agreement in the Hamaker constant values obtained by the limited Lifshitz theory and TWA approach than with the Surface energy approach. The difference is explained through the influence of surface roughness on the surface energy using extensions of the stochastic KPZ growth model and the Family-Vicsek scaling relation and rigorous treatment of the Cassie-Baxter and Wenzel models as optimisations of a surface free energy functional linking roughness and surface tension. The dominance of the Cu2O phase in the films and of the London dispersion force on the surface of the films was previously confirmed by FTIR Cu(I)–O vibrational mode observation and XPS Cu 2p 3/2 binding energy peak and its fitted satellites. The use of the limited Lifshitz theory and ellipsometry data would seem to provide a suitable best first approximation for determining the Hamaker constant of predominantly dispersive anti-stiction coatings in technologically important MEMS/NEMS devices.